Length dependent reversible off–on activation of photo-switchable relay anion transporters † - Johnson, TG; Sadeghi-Kelishadi, A; Langton, MJ (Royal Society of Chemistry, 2024)
A homologous series of azobenzene-derived photo-switchable ion relay transporters is reported. We reveal that both the length and geometry of the relay strongly affect transport rate, allowing the relative activity of the E and Z isomers to be reversed and hence the wavelengths of light used for on and off switching to be exchanged.